Considering equity in global health collaborations: A qualitative study on experiences of equity. - Marlyn C Faure (Public Library of Science (PLoS), 2021)
International collaborations have become the standard model for global health research and often include researchers and institutions from high income countries (HICs) and low- and middle-income countries (LMICs). While such collaborations are important for generating new knowledge that will help address global health inequities, there is evidence to suggest that current forms of collaboration may reproduce unequal power relations. Therefore, we conducted a qualitative study with scientists, researchers and those involved in research management, working in international health collaborations. Interviews were conducted between October 2019 and March 2020. We conducted 13 interviews with 15 participants. From our findings, we derive three major themes. First, our results reflect characteristics of equitable, collaborative research relationships. Here we find both relational features, specifically trust and belonging, and structural features, including clear contractual agreements, capacity building, inclusive divisions of labour, and the involvement of local communities. Second, we discuss obstacles to develop equitable collaborations. These include exclusionary labour practices, donor-driven research agendas, overall research culture, lack of accountability and finally, the inadequate financing of indirect costs for LMIC institutions. Third, we discuss the responsibilities for promoting science equity of funders, LMIC researchers, LMIC institutions, and LMIC governments. While other empirical studies have suggested similar features of equity, our findings extend these features to include local communities as collaborators in research projects and not only as beneficiaries. We also suggest the importance of funders paying for indirect costs, without which the capacity of LMIC institutions will continually erode. And finally, our study shows the responsibilities of LMIC actors in developing equitable collaborations, which have largely been absent from the literature.